Servitisation and technological complexity in family and non–family firms: European evidence. (1st January 2015) - Marques, Pilar; Bikfalvi, Andrea; Simon, Alexandra; Llach, Josep; Lerch, Christian
Servitisation is an emerging topic in practice and in the academy. In this paper, we address the influence of family ownership on servitisation strategy, using data collected through the European manufacturing survey, an international large–scale survey on trends in manufacturing. We approach our hypotheses through the lens of the Socio–Emotional Wealth (SEW), considering the characteristics of family firms and the rationales for servitisation. This paper provides evidence of the important role of technological factors in understanding the particular behaviour of family firms and provides empirical support for the rationales behind the SEW approach.